Effect of Some Agroforestry Situations on Incidence of Wheat Diseases under Bundelkhand Conditions - Kumar, Anil; Rai, P.; Handa, A.K. (Indian Journal of Agroforestry, 2020)
A study on effect of some agroforestry situations on incidence of wheat diseases was undertaken at National Research Centre for Agroforestry, Jhansi. Growing wheat crop with different tree species did not increase severity of locally prevalent crop diseases. Sharing of diseases, among wheat and the tree component of the systems, was not observed in this region.